DESIGN AND ANALYSIS OF CAVITATION ON 22 M SUBMARINE PROPELLERS - Indiaryanto, Mahendra; Setyanto, Taufiq Arif; Puryantini, Navik; Asrowibowo, Nurwidhi (Majalah Ilmiah Pengkajian Industri, 2020)
Many methods approach in designing a propeller for a 22 m submarine, which is based on the literature of propeller design that has been widely publicized, specifically the type B-series propeller. From the B-series propeller design, it can be known that the performance diagram in the form of the propeller coefficient is finally correlated with the 22m submarine resistance value that has been tested at BTH-BPPT. This study's objective is to produce a propeller design with good hydrodynamic aspects, especially propeller with high efficiency and cavitation phenomena that do not occur on the propeller. The implementation of this research can be done by modification on the skew angle on the B-series propeller. It is expected to choose the right B-series propeller and skew angle propeller modification, capable of providing high-efficiency values and loss of cavitation in the leaf area of the propeller. The production of propeller models is needed for conducting an open water test in the Towing Tank and the cavitation test in the cavitation tunnel at the Hydrodynamics Technology Center for the Agency for Assessment and Application of Technology (BTH – BPPT).Key Word: Design; Propeller; Cavitation